Assessment of awareness about keys of safer food among teaching and non-teaching staff in tertiary care center: a cross sectional study - Modiwala, Ashfaq; Wavare, Rajshekhar R.; Deshpande, Ajit; Kantharia, S. L. (International Journal Of Community Medicine And Public Health, 2018)
Background: Food borne diseases, usually either infectious or toxic in nature. Agents that enter the body through ingestion of food pose global health threats, endangering everyone with an underlying illness which is particularly vulnerable. The objective of the study was to assess the awareness of safe food among non-teaching and teaching staff in tertiary care center. Methods: A cross-sectional study conducted among 457 study subjects where 268 (58.6%) were Non-teaching staff and 189 (41.35%) were teaching staffs. Study subjects were those who were presently working; interviewed by using predesigned and pre-tested modified WHO pro-forma. Results: Mean percentage score for the good awareness was 60.32%. While comparing among study subjects it was found that overall awareness was higher among teaching staff. Awareness about death occurs due to food-borne diseases, followed by preventing cross-contamination by keeping separate raw and cooked food was found to be significant (p<0.05) among teaching staff while compared to non-teaching staff. Whereas rinse by running water is more practiced among (p<0.05) non-teaching staff compared to teaching staff in the study. Conclusions: The lack of awareness regarding safe food was being served as potential risk in our tertiary care center. There is an urgent need of training programme for both teaching and non-teaching staff in tertiary care center.